Moderating Effects of Gender Among Collegiate Student-Athletes Receiving a Novel Peer Concussion Education Program. (December 2021) - Kneavel, Meredith; Ernst, William; McCarthy, Kevin
Background: More than 460, 000 female and male student-athletes compete in college sports each year, with 5.5 concussions reported per 1, 000 athlete exposures. The majority of these concussions occurred during competition and are somewhat more likely to be reported by female athletes. Aims: To evaluate moderating effects of gender differences in response to a Peer Concussion Education Program (PCEP). Method: A total of 1, 100 male and 511 female student-athletes from 60 teams (30 experimental, 30 control) representing all National Collegiate Athletic Association divisions from high-concussive sports participated before, postintervention, and 1-month following the intervention. Participants completed assessments of symptom and return-to-play knowledge, reporting behavior, and reporting attitudes. Results: The PCEP was more effective than control on all measures, females in the PCEP showed significantly greater changes than males in return to play knowledge, intention to report self and teammate, and indirect attitudes for self and teammate. PCEP females were more likely to discuss concussions with athletic trainers, peers, and teammates. In addition, females had a higher likelihood of reporting their own suspected concussion. Discussion: Females had greater rates of change in understanding of some key components of the PCEP. Conclusion: These findings suggest that females may learn differently in a peer environment and have different attitudes toward reporting and safety when consideration is given to the well-being of others.